Ethical and cultural perspectives on ChatGPT use in higher education - Masroor Alam; Suchi Dubey (International Journal of Evaluation and Research in Education (IJERE), 2026)
Academic writing now faces additional challenges because users cannot identify when they use their human abilities instead of ChatGPT generative artificial intelligence (AI) tool assistance. The rapid emergence of generative AI tools such as ChatGPT has raised important ethical and cultural questions in higher education, particularly concerning authorship, originality, and responsible academic practice. The research obtained 55 open-ended survey responses from students who studied at different levels and pursued various subjects across multiple geographic areas. Among these responses, 23 provided sufficiently detailed reflections and were analyzed for qualitative insights. Using a qualitative research design, the research applied Braun and Clarke’s thematic analysis to identify three connected themes which include students’ ethical perceptions of ChatGPT use, perceived benefits and concerns in academic work, and the role of cultural context in shaping AI acceptance. Students acknowledge the helpful features of ChatGPT but they remain unclear about plagiarism rules and academic authenticity standards and institutional policies. The findings indicate that students generally perceive ChatGPT as a supportive learning tool when used responsibly, while also expressing concerns regarding dependency and unclear institutional guidance. Overall, the study highlights the need for clearer institutional policies and culturally informed AI literacy to support responsible use of generative AI in academic writing.